An application of HHI to study electricity market design issues - Tirapot Chandarasupsang (2018)
This paper presents a study of market design issues for the future Electricity Supply Industry of countries in transition from monopolistic to more competitive structures. An approach is developed to apply a standard measurement of market concentration, such as Herfindahl Hirschman Index (HHI) within the market design context. Typically, HHI is used to study market power issues in established electricity markets. The approach presented in this paper indicates that HHI can also be used as a primary method to study market design ahead of implementation. A dynamic simulation of the Thai market is used to confirm the applicability of the approach presented in this paper. Copyright © 2006 The Berkeley Electronic Press. All rights reserved.